Diabetes & Women's Health (DWH) Study: an observational study of long-term health consequences of gestational diabetes, their determinants and underlying mechanisms in the USA and Denmark. Issue 4 (1st May 2019) - Zhang, Cuilin; Olsen, Sjurdur F; Hinkle, Stefanie N; Gore-Langton, Robert E; Vaag, Allan; Grunnet, Louise Groth; Yeung, Edwina H; Bao, Wei; Bowers, Katherine; Liu, Aiyi; Mills, James L; Sherman, Seth; et al.
Abstract : Purpose: Women who experience gestational diabetes mellitus (GDM) are at exceptionally high-risk of developing type 2 diabetes (T2DM) later in life. However, limited information is available about genetic and environmental factors that are implicated in the progression from GDM to T2DM. Participants: The Diabetes & Women's Health (DWH) Study applied a hybrid design, which combined new prospective data collection with existing data in two prospective cohorts, the Danish National Birth Cohort (DNBC) and the Nurses' Health Study II (NHS II). In total, the DWH Study identified 7759 women with a GDM diagnosis from both cohorts; 4457 women participated in the DWH Study data collection, which included two cycles of follow-up from 2012 to 2014 and 2014 to 2016. Findings to date: Progression from GDM to T2DM was high. In the NHS II group, by 2013, 23.1% (n=846/3667) developed T2DM. In the DNBC group, at cycle 1 (2012–2014), the progression rate was even higher: 27.2% (n=215/790) had developed T2DM. Furthermore, we have shown that women who had GDM experienced a significantly greater risk of hypertension and cardiovascular diseases, as well as early stages of glomerular hyperfiltration and renal damage. Moreover, the DWH Study findings have shown that healthful diet and lifestyle factors and weight control were related to a lower risk of T2DM, hypertension and cardiovascular diseases. Future plans: Primary data collection for the DWH Study is complete and investigators are currently investigating interactions of the abovementioned modifiable factors with T2DM genetic susceptibility in determining the risk of progression from GDM to T2DM. Findings from ongoing work will provide further insights for identifying more precise prevention strategies for T2DM and comorbidities in this high-risk population. Future work will examine novel biomarkers of health and disease in this cohort.